UNSOLVED PROBLEMS AND PROSPECTS OF DENTAL IMPLANTATION IN PATIENTS WITH METABOLIC DISORDERS - Panahov, N.A.; Safarov, M.A.; Mammadov, F.Y. (World of Medicine and Biology, 2023)
According to the general characteristics of the study population, in total, 90 individuals were included. Among both groups, there were 50 obese patients (29 males and 21 females) and 40 non-obese individuals (23 males and 17 females) as controls. A total of 65 and 51 dental implants were placed in obese and non-obese patients. The age of obese and non-obese individuals was 31–65 years. There was no significant difference in age between both groups. All clinical parameters of inflammatory diseases of the peri-implant zone showed a statistically significant difference between groups with and without obesity. Significantly higher rates of pain syndrome, especially severe, were recorded in the main group during the observation. Such complaints increased over time in both groups, but more severe clinical manifestations of perimucositis and periimplantitis were observed against the background of metabolic disorders. In similar periods of observation in patients with overweight, more often than in the control group, a higher percentage of cases of soft facial tissues tissue edema was observed (P=0.0192). In patients with obesity, an increase in the level of patients with hyperemia of the mucous membrane adjacent to the implant zone was also more often recorded–30.0±7.25 % and 70.0±6.48 %, respectively, in the control group and in the sleep group (P=0.0001). The frequency of cases of detection of fibrinous plaque along the suture line in persons suffering from and not suffering from obesity varied. But, at the same time, statistically significant differences between the groups were found on the first day after implantation in terms of the amount of detection of gray-brown plaque. Here, the obtained data were 10.0±4.74 % and 34.0±6.70 %, respectively, in the first and second groups (Р=0.0112).